COLOR LIGHT EFFECT ON FISH CATCH RINUAK (Psilopsis sp) BY SEROK (Scoop Net) MANINJAU LAKE IN WEST SUMATRA - Ringgina Rahma Yeza; Bustari '; Arthur Brown (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted on 10 days at Maninjau Lake Waters as part, of KotoKaciak Village, Tanjung Raya District, Agam Regency, West Sumatra Province. The purposeof this study is to see the influence of light colors on rinuak fishes which is catched by serok.The method used in this study is the experimental fishing method. The research wasconducted at night and the result that there is no real difference to the influence of differentcolored lights to catch fish rinuak. Of from four light colors were applied, the red light bringthe lightest catches so much as 45% of total catch. Because the value of f 0.415> Sig. 0.743so that Ho accepted, meaning that there is no influence of the light color on rinuak (Psilopsissp) catches.Keywords: Serok, Fish Rinuak, Color lights